Studi Literatur:Upaya Penanganan Keadaan Stunting di Nusa Tenggara Timur - Atalia Pili Mangngi; Brigita Dina Manek; Ni Putu Indu Dewi Pradnyani Murti; Isna Yuswela Babys; Fitri Atapukang; Diah Ayu Dwi Satiti; Ninick Corea Fernandes; Bernadetha Erni (Pusat Riset dan Inovasi Nasional, 2025)
Stunting in children is a nutritional problem that is a national problem, this is because stunting has a negative impact on human resources in the future. Stunting is a problem because it is related to an increased risk of disease and death, less than optimal brain development so that motor development is delayed and mental growth is hampered. Stunting is a form of growth failure (growth faltering) due to the accumulation of long-term nutritional deficiencies from pregnancy to 24 months of age. The decline in stunting prevalence in Indonesia in 2024 is 14%, but this has not reached the target. Based on the 2023 Indonesian Health Survey (SKI), the prevalence of stunting in Indonesia is 21.5%. East Nusa Tenggara is the province with the highest stunting rate, namely 37.9%. Efforts to handle stunting that have been carried out are the Provision of Additional Recovery Food (ARF). Training and counseling on stunting, empowerment of cadres, to strengthen knowledge about stunting and its impacts.This study uses a literature review with data collection sources derived from scientific articles.